1995
DOI: 10.1095/biolreprod53.4.890
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ovarian Follicular Cysts and Associated Endocrine Profiles in Dairy Cows1

Abstract: It is generally accepted that ovarian follicular cysts (cysts) are nonovulatory follicular structures that contribute to extended calving intervals. Follicle/cyst dynamics and the etiology of cysts are unclear. The present study was conducted to characterize follicle/cyst dynamics and to define endocrine changes (etiology) associated with cyst development. Thirty-two dairy cows were studied: controls (n = 6), cows with spontaneously occurring cysts (n = 14), and cows in which cysts were induced by exogenous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
141
2
5

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(159 citation statements)
references
References 25 publications
11
141
2
5
Order By: Relevance
“…Ultrasonography has proved to be useful in monitoring the dynamics of experimental ovarian cyst formation following the administration of steroids in heifers and cows [111][112][113][114]. Cyst turnover in spontaneous occurring ovarian cysts in cows [115] was also monitored.…”
Section: Ovarian Cystsmentioning
confidence: 99%
“…Ultrasonography has proved to be useful in monitoring the dynamics of experimental ovarian cyst formation following the administration of steroids in heifers and cows [111][112][113][114]. Cyst turnover in spontaneous occurring ovarian cysts in cows [115] was also monitored.…”
Section: Ovarian Cystsmentioning
confidence: 99%
“…Cook et al [4] reported that steroid-induced follicular cysts in cattle were not static structures, but regressed to be replaced with other cystic structures. Furthermore, previous investigations [7,17] showed that spontaneously occurring ovarian cysts also exhibit a turnover of cysts, and suggested that the absence of a preovulatory surge of luteinizing hormone (LH) causes ovarian cysts [3,7,17].Approximately 20% of cows with ovarian cysts recover spontaneously within 30 days following diagnosis [1]. The turnover of cysts and associated changes of plasma gonadotropins and ovarian steroids in cows with spontaneously occurring ovarian cysts have been reported [17], but they have not been reported in cows which recovered from ovarian cysts or then relapsed into cysts.…”
mentioning
confidence: 92%
“…Cook et al [4] reported that steroid-induced follicular cysts in cattle were not static structures, but regressed to be replaced with other cystic structures. Furthermore, previous investigations [7,17] showed that spontaneously occurring ovarian cysts also exhibit a turnover of cysts, and suggested that the absence of a preovulatory surge of luteinizing hormone (LH) causes ovarian cysts [3,7,17].…”
mentioning
confidence: 99%
See 2 more Smart Citations